Searching for Embodied Presence in Architecture - Cruz, Marlon Gutierrez (My University, 2020)
Buildings have the capacity to affect our emotions. When designed with care, they can move us and put us into a state of emotional awareness that heightens our everyday experience of living. But unfortunately, a building’s ability to elicit any kind of meaningful emotional response is a rare quality. More often than not, buildings tend to take on qualities of passive functionality that lose sight of the potential they have to move the human spirit. We tend to experience most buildings in a kind of unconscious haze as a result, frequently becoming absent-minded in our day-to-day rituals of life. We are surrounded by buildings and utilize them on a daily basis, and yet, very few have meaningful qualities that can register a kind of consciousness that leaves us with a lasting impression. Why is this? What separates those buildings we tend to disregard and those which move us internally? The answer lies in a building’s ability to embody presence. Presence is a quality not easily defined, but it goes beyond the superficialities of external form and instead, focuses on certain core principles which bring the building and the human experience in harmony. When a building has presence, it moves us emotionally and creates a consciousness of existence that arises in large part from its capacity to satisfy our innate human behaviors and drives. Architect Louis Kahn once wrote, “A great building, in my opinion, must begin with the unmeasurable, must go through measurable means when it is being designed, and in the end must be unmeasurable.” This is the concern of this thesis: to identify those essential principles that contribute to the feeling of presence in space. It is an attempt to define those “measurable means” that can get us closer to the elusive qualities of the “unmeasurable”. The principles in this thesis are what I believe to be those qualities that can move us and transform buildings into works of architecture.
Thesis (Master's)--University of Washington, 2019
Keywords: Making; Materials; Phenomenology; Presence; Principles; Tectonics; Architecture; Architecture